Potencial antigenotóxico e anticitotóxico de compostos fenólicos utilizando peçonhas de serpentes como ferramentas indutoras de danos - Abreu, Tatiane Silva de (2017)
Phenolic compounds have pharmacological activities that contemplate mechanisms of inhibition or inductions of DNA molecules degradation. Genotoxic damages can be induced by venom or occur naturally. Natural compounds can act as enzymatic inhibitors through a connection to hydrophobic sites present in the structures of some enzymes or to catalytic sites, neutralization of reactive species or suppression of their generation, sequestration of ions corresponding to enzymatic cofactors, or competition for solvation water of enzymes triggering the precipitation and inactivation of these enzymes. Aiming to investigate the protective action of phenolic compounds, caffeic acid (AC), gallic acid (GA), syringic acid (AS) and vanillic acid (AV) on enzyme induced cytogenetic damage were used as tools to induce venom Bothrops atrox, B. jararacussu and Lachesis muta muta. The electrophoretic profile (SDS-PAGE) of incubations containing venoms and phenolic compounds suggests the presence of molecular interactions of these, with toxins present in venoms. Agarose gel electrophoresis allowed to evaluate the human leukocyte DNA fragmentation induced by snake venoms as well as the antigenotoxic action of phenolic acids when previously incubated with venoms. The comet test performed with human leukocytes showed that the phenolic compounds evaluated, in high doses, can induce DNA fragmentation as well as potentiate the genotoxic action exerted by the toxins present in the venoms. In the Krebs cycle succinate dehydrogenase inhibition assay, CA and GA acted to potentiate inhibition the action of malic acid in some at doses, whereas for AS and AV, there were no significant differences in potentiation or reversal of inhibition caused by the inhibitor (malonate) on a succinate dehydrogenase. The partial characterization of these compounds, carried out in the present work, complements previous studies on these molecules that have high potential for future therapeutic applications, and it is also necessary to prospect formulations and safe administration forms for human consumption, since safe daily consumption values have already been previously defined by ANVISA. The activities evaluated in the present study suggest possible applications of these compounds alone, or plant extracts that present these molecules in their composition, in the complementation of traditional antiophidic serum therapy or in its substitution, as well as in the prevention and treatment of inflammatory, digestive, neurodegenerative and several others that are associated to the action of proteases, phospholipases and oxidases in general of great value in the medical-scientific scope.